Clozapine disposition covaries with CYP1A2 activity determined by a caffeine test. - Bertilsson, L (1994)
In a previous study we showed that the disposition of clozapine after a single oral dose is unrelated to either debrisoquine or S-mephenytoin hydroxylation polymorphism. The same 14 healthy subjects studied in that investigation were given 150 mg of caffeine. The reciprocal of plasma clozapine AUC (0,24), was correlated with an index of the N3-demethylation of caffeine (rs = 0.84; P = 0.0024), used as a measure of cytochrome P4501A2 (CYP1A2) activity. N1- and N7-demethylation indices of caffeine also reflect CYP1A2 activity and were also correlated with clozapine clearance (rs = 0.89 and 0.85; P = 0.0013 and 0.0023; respectively). No significant relationships with xanthine oxidase and N-acetyl transferase activity, also assessed by a caffeine test, were found. This study suggests that clozapine is metabolised by CYP1A2 to a major extent.